How many species of Paradoxurus civets are there? New insights from India and Sri Lanka. (3rd November 2014) - Veron, Géraldine; Patou, Marie‐Lilith; Tóth, Mária; Goonatilake, Manori; Jennings, Andrew P.
Abstract Using molecular data and morphological features, we investigated the species limits and genetic diversity among populations of the Asian palm civets of the genus Paradoxurus. Our main objectives were to determine the number of species within Paradoxurus hermaphroditus and to test the validity of the newly proposed species within Paradoxurus zeylonensis. Fragments of two mitochondrial (Cytochrome b, Control Region) and one nuclear (intron 7 of the beta fibrinogen) markers were sequenced from 128 individuals of P. hermaphroditus, P. zeylonensis and Paradoxurus jerdoni. DNA sequences were analysed using phylogenetic and haplotype network methods. Our analyses confirmed that P. hermaphroditus comprises three major clades, which should be recognized as separate species: P. hermaphroditus (Indian and Indochinese regions), Paradoxurus musangus (mainland Southeast Asia, Sumatra, Java and other small Indonesian islands) and Paradoxurus philippinensis (Mentawai Islands, Borneo and the Philippines). Furthermore, we have proposed that there are two subspecies within both P. musangus and P. philippinensis, and there might be at least two or three subspecies within P. hermaphroditus. We found a very low genetic diversity and no geographical structure within P. zeylonensis and did not find any support for splitting P. zeylonensis into several species nor subspecies. Finally, we confirmed that P. jerdoni and P. zeylonensis are sister species.